Comparison of Two Different Techniques for Isolated Left Subclavian Artery Revascularization During Thoracic Endovascular Aortic Repair in Zone 2. (December 2018) - Piffaretti, Gabriele; Pratesi, Giovanni; Gelpi, Guido; Galli, Mario; Criado, Frank J.; Antonello, Michele
Purpose: To analyze the results of isolated left subclavian artery (LSA) revascularization during thoracic endovascular aortic repair (TEVAR) using carotid-subclavian bypass (CSbp) or chimney grafts (CGs).Methods: A retrospective multicenter, observational study identified 73 patients (mean age 68±13 years, range 22–87; 56 men) with acute or chronic thoracic aortic lesions who underwent TEVAR with isolated LSA revascularization using either CSbp (n=42) or CGs (n=31) from January 2010 and February 2017. Primary endpoints were TEVAR-related mortality, postoperative stroke, freedom from type Ia endoleak, and LSA patency.Results: Primary technical success was achieved in all cases. Early TEVAR-related mortality was 4.2% (CSbp 2% vs CG 6%, p=0.571). Two (3%) patients had major ischemic strokes (one in each group). Mean follow-up was 24±21 months (range 1–72; median 15). Estimated freedom from TEVAR-related mortality was 93%±3% (95% CI 84.3% to 97.0%) at 12 and 36 months, with no significant difference between CSbp and CG (p=0.258). Aortic reintervention did not differ between the groups (CSbp 5% vs CG 6%, p=0.356); nor did freedom from type Ia endoleak (CSbp 98% vs CG 87%, p=0.134). Gutter-related endoleaks occurred in 4 (13%) CG patients, but none of the patients experienced sac enlargement or the need for reintervention and none died. Primary patency of the LSA was 100% for the entire group during the observation period.Conclusion: In our experience, LSA revascularization proved most satisfactory and equally effective with both the CSbp and CG techniques, without discernible differences at midterm follow-up.